Impact of the Revised Malaysian Code on Corporate Governance on Audit... (Global Journal of Management and Business Research, 2016)
Using a sample of 37 finance companies listed under the finance segment of Bursa Malaysia, we examined the impact of the revision to Malaysian code on corporate governance on audit committee attributes and firm performance. Our result suggests that audit committee attributes significantly improved after the Code was revised. In addition, the coefficient for audit committee and risk committee interlock has a significant negative relationship with Tobin's Q in the period before the revision to the Code and before the global financial crisis. The negative direction of the result is contrary to agency theory which suggests that separating directors on subcommittees will create information asymmetry between the directors and lead to poor coordination in the decisions of the committees thereby negatively affecting firm performance.
Keywords: corporate governance; audit committee; independent directors; expert directors; performance; executive membership; directors interlock; malaysian code